Prevalence of Hypovitaminosis D in Patients Visiting a Tertiary Care Center in Chitwan, Nepal - Bhattarai, Kushal; Manandhar, Nilu; Dhakal, Sarita (Journal of College of Medical Sciences-Nepal, 2019)
Background: As documented by a large body of evidences, Hypovitaminosis D prevails both in the general and the hospitalized populations. We conducted this study to determine the prevalence of hypovitaminosis D amongst the patients visiting a tertiary care hospital and compare the rate gender-wise, across different categories of socio-demographic variables. Methods: It was a cross-sectional study (retrospective chart review) based on the hospital registry of patients at College of Medical Sciences and Teaching Hospital, Bharatpur, Chitwan, Nepal. From the registry, we retrieved the socio-demographic variables (age, gender, ethnicity and season) along with serum vitamin D (25-hydroxy-cholecalciferol) concentrations of the study subjects from January 2015 to August 2018, for our analysis. Hypovitaminosis D was defined as serum vitamin D <30 ng/mL (insufficiency: 20-30ng/mL and deficiency: <20 ng/mL). Results: The overall prevalence of hypovitaminosis D was 70.7% (insufficiency: 35.9% and deficiency: 34.8%), 72.4% (females), 64.2% (males), 76.3% (first age-quartile), 74.5% (miscellaneous ethnic group), and 73.9% (Spring). Females had higher prevalence rates of hypovitaminosis D (and lower median serum 25-hydroxy-cholecalciferol lev-els) as compared to males, in overall participants, and those under each category of age, ethnicity and season (except Winter). Conclusions: The greater prevalence of hypovitaminosis D in the females than the males in the face of high rate in the overall hospital-visiting clearly calls for necessary strategies in the form of further studies and judicious prescription of supplementary vitamin D in the target population.